Recent advances in surface-active ionic liquid-assisted self-assembly systems for drug delivery - Moshikur, R.M. (Elsevier Ltd, 2021)
Surface-active ionic liquids (SAILs) are receiving growing interest as environmentally friendly designer surfactants for various applications, including drug formulation and delivery. The use of SAILs in the pharmaceutical industry has the potential to address the challenges associated with conventional surfactants. The tunable formation of complementary ion pairs from a diverse range of ions enables the task-specific optimization of SAILs. SAILs comprising second and third-generation cations and anions have been used to design biocompatible self-assembled systems including micelles, microemulsions, vesicles, liposomes, and nanoparticles for drug delivery carriers. Compared with conventional surfactant-based carriers, SAIL-based systems offer better pharmacokinetic and pharmacodynamic properties. This mini-review highlights recent findings on the formation of ionic liquid-based self-assembled systems and their potential applications in drug delivery. Â© 2021 Elsevier Ltd